Features of the in-hospital course of myocardial infarction in patients with glucose metabolism disorders - B. U. Mardanov; M. N. Mamedov; M. N. Korneeva; R. G. Oganov (Столичная издательская компания, 2015)
Aim. To study the clinical course of acute myocardial infarction (MI) with ST segment elevation (STEMI) and the features of inpatient treatment in patients with and without diabetes mellitus (DM). Material and methods. STEMI patients (n=83), who were hospitalized in 2014, were included into the study. The patients were divided into two groups according to the presence or absence of glucose metabolism disorders: Group 1 (patients with type 2 DM; n=38) and Group 2 (patients without glucose metabolism disorders; n=45). Baseline demographic, clinical, laboratory and instrumental characteristics of the patients, along with the features of hospital treatment, were studied.  Results. In group 1 compared with group 2 hypertension was detected significantly more frequently (73.7% vs 49%; p<0.05), and a class of acute heart failure (Killip) at admission was higher (1.46±0.6 vs 1.23±0.57; p<0.05). STEMI was complicated by an acute left ventricular aneurysm 12% more often in patients of group 1 (p<0.05). The duration of inpatient treatment was also higher in patients of group 1 (18±4.1 vs 16±3.6 days; p<0.05). Conclusion. Only 21% of the patients with DM and STEMI had adequate treatment of ischemic heart disease and a quarter of the patients in this group had no adequate DM therapy before the admission. Patients with DM had a higher incidence of in-hospital STEMI complications and a higher duration of inpatient treatment.